Ultra-Wideband Terahertz Absorption Using Dielectric Circular Truncated Cones - Longfang Ye; Xin Chen; Fang Zeng; Jianliang Zhuo; Fei Shen; Qing Huo Liu (IEEE Photonics Journal)
We numerically demonstrate an ultra-wideband terahertz absorber using dielectric circular truncated cones on a non-structured graphene layer supported by a dielectric spacer on a metal reflector in the bottom. The absorber has an ultra-wideband absorption bandwidth from 0.34 to more than 10 THz with an average absorbance of 95.88% and a relative bandwidth of 186% because of the continuous multimode Fabry-Perot (FP) resonances. The absorber also possesses excellent absorption characteristics with polarization independence under normal incidence and angular stability up to 60°. The proposed ultra-wideband absorber may have promising applications in terahertz trapping, imaging, and detecting.